SIMULATOR LENGAN ROBOT ENAM DERAJAT KEBEBASAN MENGGUNAKAN OPENGL - Balza Achmad; Musthofa Sunaryo; Agus Arif (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2008)
A robot simulator has been developed, that capable in simulating a 6 degree of freedom robot manipulator. Using this simulator, a user can define the type and angular range of the joints, and length of each link, as well as the colors. User can also select an arbitrary viewing angle and move the robot manually or automatically. The simulator was developed using C++ programming language utilizing OpenGL graphic library. Denavit-Hartenberg notation was used as parameters to specify the shape and size of the manipulator.